A hybrid electromagnetism-like algorithm for a multi-mode resource-constrained project scheduling problem - Mohammad Hossein Sadeghi; Reza Tavakkoli-Moghaddam (مدیریت تولید و عملیات, 2013)
In this paper, two different sub-problems are considered to solve a resource constrained project scheduling problem (RCPSP), namely i) assignment of modes to tasks and ii) scheduling of these tasks in order to minimize the makespan of the project. The modified electromagnetism-like algorithm deals with the first problem to create an assignment of modes to activities. This list is used to generate a project schedule. When a new assignment is made, it is necessary to fix all mode dependent requirements of the project activities and to generate a random schedule with the serial SGS method. A local search will optimize the sequence of the activities. Also in this paper, a new penalty function has been proposed for solutions which are infeasible with respect to non-renewable resources. Performance of the proposed algorithm has been compared with the best algorithms published so far on the basis of CPU time and number of generated schedules stopping criteria. Reported results indicate excellent performance of the algorithm.